Fundamentals Of Entrepreneurship (ENT300) : Case study Cotton On Group Selling / Ahmad Shadiqin Ali Rahman … [et al.]. - Ahmad Shadiqin, Ali Rahman; Dennis, Vivian Gulang; Tony, Muhammad Dzikry; Abg Zolfaka, Dyg Nur Zinnirah; Sabarin, Nur Izzah
In this case study, we had interviewed the company of our choice, which is Cotton On. Based on the interview, we had discussed on various topics that will be elaborated further in this case study. Firstly, we discuss the purposes of learning entrepreneurship in this course and what it takes to be an entrepreneur, as well as numerous problems that people face when opening a business.